Out-of-plane vibrations of shear deformable continuous horizontally curved thin-walled beams - Piovan, Marcelo Tulio (2000)
This paper presents numerical study about the influence of the shear flexibility, due to either bending and warping, on the out-of-plane free vibration of continuous horizontally curved thin-walled beams with both open and closed sections. This study was made by means of a recently developed finite element formulation for shear deformable curved thin-walled beams. The model is briefly reviewed and is used to obtain natural frequencies of continuous I-beams and box beams. A parametric study was performed in order to elucidate the influence of shear deformability, on the dynamic behavior of continuous thin-walled curved beams, for different slenderness ratios, cross-sectional characteristics and boundary conditions.